Poškodbe tal po strojni sečnji in spravilu lesa z zgibnim polprikoličarjem - Mali, Boštjan (Gozdarski vestnik, 2007)
The authors discuss soil damage after mechanized cutting followed by skidding with forwarder. Two research sites were chosen - one in the management unit GEMirna gora (dolomite bedrock) and another in the unit Radeče (silicate bedrock). In Mirna gora data was recorded along transects on constructed skid roads, designated skid trails and harvester trails prior to and following skidding, and the soil bearing capacity was also measured using the penetrometer Dickey John. On the site at Radeče, data was recorded along transects only after cutting and skidding, but this was due to an easier and less configurated terrain. The thickness of logging residues on trails was also determined. Analyses showed changes in soil density after skidding and pointed out the significance of logging residues on trails. Rut depth was compared to values which are standard abroad.
Keywords: strojna sečnja; gozdna tla; poškodbe tal; spravilo lesa